STUDENT’S LEARNING EXPERIENCE WITH ELSA SPEAK IN AI-ASSISTED PROJECT-BASED LEARNING FOR SPEAKING - Pasaribu, Nurhayati; Kusrin; Setia Samsi, Yogi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of Artificial Intelligence (AI) into English language learning has the potential to improve speaking skills. However, research on students’ learning experiences with ELSA Speak in AI-Assisted Project-Based Learning (PjBL) at the junior high school level remains limited. This study aims to explore students’ learning experiences with ELSA Speak in speaking instruction. The study employed a qualitative approach involving eight eighth-grade students at a junior high school in Karawang. Data were collected through semi-structured interviews and analyzed using the Miles, Huberman, and Saldaña model. The results revealed four main themes: positive learning experiences, benefits to speaking skills, AI-supported learning processes, and challenges encountered during learning. ELSA Speak helps improve students’ pronunciation, speaking fluency, self-confidence, and readiness to complete projects. Although there were some obstacles, the students felt that the benefits of using ELSA Speak outweighed the challenges they faced. These findings suggest that ELSA Speak has the potential to support more interactive and student-centered speaking instruction. Overall, ELSA Speak can support more interactive and student-centered speaking instruction within AI-Assisted Project-Based Learning. English teachers are encouraged to integrate AI-based applications into project-based speaking activities to provide students with more opportunities for independent practice and immediate feedback.